Comparative evaluation of efficiency and fit analysis for the bodice pattern Armstrong vs Aldrich vs Bunka - Martinez, Jan Paul S. (College of Home Economics, University of the Philippines Diliman, 2023)
Pattern making involves the manipulation of paper or fabric to conform the contours of the human body. According to Aldrich (2015), block patterns serve as the foundation for patternmaking for design adaptations. However, instructions and fit quality vary across different patternmaking methods, thus, the objectives of this study aimed to evaluate the efficiency and fit quality of the Armstrong, Aldrich, and Bunka-style sloper methods, to determine their required measurements, number of steps, and fit characteristics to assist students in determining the most effective pattern making method appropriate for their skill level. The study explored the different methods in drafting the sloper for a medium-sized bodice without sleeves. The research used non-probability, convenience sampling. First, the researcher listed down the upper body measurements and patternmaking instructions according to the instructions stated in each book. This resulted in 25 measurements required for the Armstrong method, 10 for Aldrich, and 3 for Bunka as well as 91 steps for Bunka, 72 for Armstrong, and 65 for Aldrich. Muslin fabric and a control dress form were used to keep measurements constant. Quantitative data in the form of body measurements from the dress form were collected according to specifications from each book. Then the researcher drafted 3 basic front and back bodices and created test garments based on the instructions of each book. Qualitative data on each method's fit quality was collected from the test garments through the use of an observation checklist. Quantitative and Qualitative analysis revealed that the Armstrong method, with the most comprehensive instructions and diagrams, is recommended for novice college students while the Aldrich and Bunka methods were ideal for beginners and more experienced dressmakers, respectively. The researcher recommends exploring other basic blocks, conducting similar studies encompassing various body sizes, and further research involving real human subjects.